Periodic Points of Modular Firmly Mappings in the Variable Exponent Sequence Spaces ℓp(·) - Afrah A. N. Abdou; Mohamed A. Khamsi (Mathematics, 2021)
In this work, we investigate the existence of periodic points of mappings defined on nonconvex domains within the variable exponent sequence spaces <semantics>ℓp(·)</semantics>. In particular, we consider the case of modular firmly nonexpansive and modular firmly asymptotically nonexpansive mappings. These kinds of results have never been obtained before.